Clinical Outcomes of Primary Posterior Continuous Curvilinear Capsulorhexis in Postvitrectomy Cataract Eyes. (31st July 2020) - Yu, Mengting; Yan, Duan; Wu, Wenjie; Wang, Yingbin; Wu, Xinna
Abstract : Purpose . To evaluate the safety and outcomes of primary posterior continuous curvilinear capsulorhexis (PPCCC) combined with phacoemulsification in postvitrectomy eyes. Design . Retrospective case series. Methods . Twenty-one postvitrectomy eyes of 21 patients with cataract between April 2017 and December 2019 were enrolled. PPCCC through the cornea incision was performed before in-the-bag intraocular lens implantation. All patients were followed up for at least 3 months postoperatively. The outcome measures were corrected distance visual acuity (CDVA), intraocular pressure (IOP), corneal endothelium cell counts (CECC), central macular thickness (CMT), the occurrence of intraoperative or postoperative complications, and the incidence of posterior capsular opacification (PCO). Results . The mean age was 56.14 ± 9.76 years (ranging from 31 to 68). The mean Snellen CDVA was 20/400 preoperatively and improved to 20/67 postoperatively P < 0.001 . No significant differences were found between IOP P = 0.96 and CMT P = 0.42 preoperatively and postoperatively. The mean CECC was 2571.8 ± 319.3 cells/mm 2 preoperatively and 2498.2 ± 346.3 cells/mm 2 postoperatively P < 0.05 . Lens epithelium cells proliferation was confined to the peripheral capsular bag during a mean follow-up of 12.9 ± 10.5 months (ranging from 3 to 28 months). Intraoperative posterior capsule extension occurred in 1 eye (4%), although it did not affect the patient's vision. No serious complications, including retinal detachment or endophthalmitis, were detected in any of the 21 cases. Conclusion . PPCCC through cornea incision combined with phacoemulsification may be a safe and practical alternative to prevent PCO in postvitrectomy eyes with cataract.